Multimodality Imaging in the Assessment of Thoraco-Omphalopagus Conjoined Twin: Lessons to Learn. (6th June 2012) - Chelliah, Kanaga Kumari; Faizah, M. Z.; Dayang, A. A.; Bilkis, A. A.; Shareena, I.; Mazli, M.
Abstract : Conjoined twins are rare and present a unique challenge to pediatric surgeons and radiologists. An imaging strategy to accurately define anatomic fusion, vascular anomalies, and other associated abnormalities is important for surgical planning and prognostic information. A conjoined female twin with a combined weight of 2.8 kg was born by emergency caeserean. Hence, a computed tomography scan of the thorax and entire abdomen at 1.25 mm slice thickness was performed to delineate the internal structures of the twins. CT-angiography defined specific vascular supply which determined the distribution of shared structures between the twins. An echocardiogram showed four heart chambers with atrioventricular septal defect. To further evaluate the heart chambers, the twin was planned for gated cardiac magnetic resonance imaging. Unfortunately, they succumbed 6 hours apart due to complication of septicemia. Magnetic resonance imaging and CT scan provide excellent anatomic detail, demonstrating organ position, shared viscera, and limited vascular anatomy, whilst angiography defined specific vascular supply, useful in determining the distribution of shared structures between the twins in planning for surgery.